2013
DOI: 10.3111/13696998.2013.852098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient-reported non-severe hypoglycemia on healthcare resource use, work-time loss, and wellbeing in insulin-treated patients with diabetes in seven European countries

Abstract: NSHE were associated with use of extra healthcare resources and work-time loss in all countries studied, suggesting that NSHE have considerable impact on patients/society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 24 publications
6
57
0
1
Order By: Relevance
“…Further, since each domain of the TRIM-HYPO has been validated as well as the total score, the The concept elicitation phase of the TRIM-HYPO development clearly confirmed not only the broad spectrum of domains that are impacted by these events, but also that the severity of these impacts can be very detrimental to patients' daily functioning and well-being. These findings confirm findings from prior studies that have reported major and life disruptive impacts of non-severe hypoglycemic events [35,36]. Further, the validation phase of the TRIM-HYPO development found that the measure can be considered well validated as the PCA confirmed the preliminary theoretical framework, the item-to-domain correlations, and the overall fit statistics showed high item reliability coefficients, indicating that each of the TRIM-HYPO domains is a reliable measure with a good spread placement of items along the scale.…”
Section: Discussionsupporting
confidence: 93%
“…Further, since each domain of the TRIM-HYPO has been validated as well as the total score, the The concept elicitation phase of the TRIM-HYPO development clearly confirmed not only the broad spectrum of domains that are impacted by these events, but also that the severity of these impacts can be very detrimental to patients' daily functioning and well-being. These findings confirm findings from prior studies that have reported major and life disruptive impacts of non-severe hypoglycemic events [35,36]. Further, the validation phase of the TRIM-HYPO development found that the measure can be considered well validated as the PCA confirmed the preliminary theoretical framework, the item-to-domain correlations, and the overall fit statistics showed high item reliability coefficients, indicating that each of the TRIM-HYPO domains is a reliable measure with a good spread placement of items along the scale.…”
Section: Discussionsupporting
confidence: 93%
“…Data on costs of healthcare resource use (preventive treatment, micro-and macrovascular complications) were retrieved from scientific publications [17][18][19][20][21] ; and from online databases, official pricelists and public agency reports [22][23][24][25][26] . A detailed specification of costs and prices is found in Supplemental material, Tables S2-S7.…”
Section: Costs Of Healthcare Resource Use and Loss Of Productionmentioning
confidence: 99%
“…The economic burden associated with hypoglycemia is also substantial, with acute use of healthcare resources through HErelated emergency room (ER) visits, hospital admittance and in the longer term, indirectly as a result of the increased risk of complications such as cardiovascular diseases, which carries a heavy cost burden [5,11]. The Incidence and cost of hypoglycemic events requiring medical assistance in a hospital setting in Denmark increased risk of cardiovascular disease may stem from a number of factors, such as weight gain and/or due to the release of catecholamines locally in the heart during HEs [5].…”
Section: Introductionmentioning
confidence: 99%